Dewi Saraswati sebagai Sumber Ide Penciptaan Busana Ready To Wear “Gantari” - Elsi Hayuning Trias; Hapsari Kusumawardani; Endang Prahastuti; Annisau Nafiah (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The creation of this work is based on the existence of Dewi Saraswati as the goddess of science and art in Hindu beliefs as the main inspiration due to the researcher’s interest in culture and history so that she intends to put it into a fashion work as a form of creativity in designing a fashion collection. The process of creating this fashion work is based on the practice-led research approach through the study of fashion design practice, focusing on Dewi Saraswati as the main inspiration for the fashion creation. The combination of dark and light colors from the bold lurik fabric motifs as well as the rustic theme reinforced by the addition of macrame shows the figure of the Goddess who is authentic, beautiful and close to nature. The name Gantari, which in Sanskrit means to shine, is a representation of Dewi Saraswati’s role on earth, namely as a manifestation of Ida Sang Hyang Widi (God in Hinduism) to guide humans on earth who live in darkness due to ignorance and confusion before the existence of science. In addition, the addition of details in the form of embroidered puppets in the form of Dewi Saraswati became the main point of this Gantari dress. The method of creating this work was carried out through four stages including the pre-design stage, design, realization, and the last is the presentation stage. The result of Gantari’s creation was two works of ready to wear deluxe fashion presented in the UM 2023 Fashion Education Grand Show with a cat walk fashion show presentation form.